PEDAGOGICAL SIGNIFICANCE OF THE APPLICATION OF INNOVATIVE PEDAGOGICAL TECHNOLOGIES IN HIGHER EDUCATIONAL INSTITUTIONS - Mardonov Ruslanjon Boymurad ugli (Modern American Journals, 2025)
This article presents a pedagogical classification of innovative technologies and related concepts in technological education in higher education institutions.
Keywords: Innovative technology, pedagogical process, pedagogical software tools, information communication technologies.